Pengaruh bahan kampas rem terhadap respon getaran pada sistem rem cakram - Muhammad Mushlih Elhafid; Didik Djoko Susilo; Purwadi Joko Widodo (Badan Kerja Sama Teknik Mesin Indonesia, 2017)
This study aims to determine the effect of brake pads material to the vibration response of disc brake system on many variety of braking conditions. The variations of brake pads material on this research such as metallic, non-asbes and ceramic. The variations of braking operation such as speed of disc rotation and braking pressure. Each brake pads material tested by variation of disc rotation 425, 637, 850, 1062 rpm and pressure variation 0,5 bar, 1 bar, 1,5 bar. Furthermore, the dynamic characteristics of brake pad had been tested by using the method of Modal Analysis Experiment. The results showed that the type of brake pad materials, disc rotation and braking pressure affect to vibration response of disc brake system. Increasing speed of disc rotation and braking pressure will increase the excitation force causing value amplitude of vibration in the braking system increases. Usage of brake pad ceramic also showed the lowest amplitude of vibration for all variations of disc rotation and braking pressure. Because the ceramic brake pad have the lowest natural frequency, then the value of the damping ratio is high, so that decreasing amplitude of vibration that occurs in the braking system.